Efficacy of remote ischaemic preconditioning for spinal cord protection against ischaemic injury: association with heat shock protein expression - Selimoglu, Ozer; Ugurlucan, Murat; Basaran, Murat; Gungor, Funda; Banach, Maciej; Cucu, Oguzcan; Ong, Lee Lee; Gasparyan, Armen Yuri; Mikhailidis, Dimitri; Ogus, Temucin Noyan (Folia Neuropathologica, 2008)
Introduction: We aimed to determine the efficacy of remote ischaemic preconditioning in the hind limb of rats for ischaemic damage of the spinal cord through neurological and histological investigation and examination of heat shock proteins (HSP). Material and Methods: Thirty male Sprague-Dawley rats were divided into three groups as Group 1 (control group, n=10), Group 2 (ischaemia control group, n=10), and Group 3 (remote ischaemia preconditioning group, n=10). The right lower limb of the rats in the study group was compressed with a tourniquet for three cycles of ten-minute ischaemia followed by ten-minute reperfusion. After a period of 8 hours, the peritoneal cavity was accessed through a midline vertical incision. The abdominal aorta was clamped between the origin of the renal arteries and the iliac arteries for 45 minutes and spinal cord ischaemia was induced. The same procedure of abdominal aorta clamping was performed in the control group without creating leg ischaemia. The rats were evaluated for neurological parameters at 24 and 48 hours. At the end of this time period, all rats were sacrificed and the spinal cords were stained for determination of HSP and histopathological classification. For immunohistochemical evaluation, the samples were analyzed according to the degree of staining with HSP70 rabbit antibody. Results: After completing the neurological examinations and histological evaluations, we determined the spinal cords of the animals in the sham group to be completely normal. The post-operative neurological examination scores of Group 3 at 24 and 48 hours were significantly higher than scores measured in the other two groups. There were seven rats with HSP expression and this was detected in animals pretreated with remote ischaemic preconditioning. There were also two rats in Group 2 with HSP expression. Conclusion: Our results show that production of transient remote ischaemia preconditioning in the lower extremities reduces damage in the spinal cord secondary to ischaemia probably by the increase of HSP.